PENDIDIKAN KEAKSARAAN DI INDONESIA KE DEPAN - Napitupulu, W. P. (JIV-Jurnal Ilmiah Visi, 2007)
Quoting EFA Global Monitoring Report 2006 on literacy for life, this article discusses its implementation in Indonesia. It is believed that the success of the literacy program is closely related to the government policy. Based on the analysis of the condition and problems of illiteracy, the political leaders of the highest level are expected to be committed to take real actions, all nations including Indonesia formulate and implement written and explicit literacy policy in developing access to basic education, conduct continuous literacy program. In conclusion, the article suggests the Indonesian Government, as a member of United Nations, should tightly keep the commitment expressed in a number of UN’s declarations and conferences including to achieve the goals in The United Nations Literacy Decade 2003 – 2012.